MELT- VERSUS FLUID-INDUCED METASOMATISM IN SPINEL TO GARNET WEDGE PERIDOTITES (ULTEN ZONE, EASTERN ITALIAN ALPS): CLUES FROM TRACE ELEMENT AND LI ABUNDANCES - Scambelluri M.; Rampone E.; Hermann J.; Morten L. (My University, 2006)
The peridotite bodies of the Ulten Zone (Upper Austroalpine, Italian Eastern Alps) are enclosed in Variscan migmatites and derive from a mantle wedge environment. They display the progressive transformation of porphyroclastic spinel peridotites (T =1,200 °C; P =1.5 GPa) into fine-grained garnet-amphibole peridotites (T =850 °C; P =3 GPa). Detailed bulk-rock and mineral trace element analyses of a sample suite documenting the entire metamorphic evolution of the peridotites revealed several stages of metasomatism. The spinel peridotites derive from a depleted mantle that became enriched in some large ion lithophile element (LILE) and light rare earth elements (LREE). The same signature pertains to clinopyroxene and orthopyroxene, indicating that this metasomatic signature was acquired at the recorded temperature of 1,200°C. Such a temperature is considerably above the wet peridotite solidus and hence the metasomatic agent must have been a hydrous melt. Moreover, the Li-enrichment of the spinel-facies pyroxenes (up to 24 ppm Li) reflects disequilibrium distribution after exchange with a presumably mafic melt. cpx/opx DLi=3-7 and cpx/ol D Li=2.7-8 indicate that the spinel-facies clinopyroxene hosts higher Li amounts than the coexisting minerals. LREE fractionation, variable LREE enrichment, LILE enrichment with respect to HFSE (average clinopyroxene PbN/NbN=16-90) in spinel lherzolites can be related to chromatographic effects of porous melt flow. The significant enrichment of pyroxenes from the spinel lherzolites in Pb, U and Li indicates that the metasomatic melt was subduction-related. All these features suggest that the spinel lherzolites formed a mantle wedge layer percolated by melts carrying recycled crustal components and rising from a deeper source of subduction magmas. The garnet-amphibole peridotites equilibrated at temperatures well below the wet solidus in the presence of an aqueous fluid. Bulk-rock trace element patterns display pronounced positive anomalies in Cs, Ba, Pb and U and moderate enrichment in Li, indicating addition of a crustal component to the mantle rocks. Amphibole hosts most of these trace elements. Clinopyroxene displays high LILE/HFSE (PbN/NbN=300-600), low Ce/Pb (1.4-2.7 in garnet-facies clinopyroxene compared with 2.6-24.5 in the spinel-facies one) and variable LILE and LREE enrichments. The coupled increase of modal amphibole, Sr and Pb, together with positive Pb-Sr and Pb-U correlations, further indicate that incompatible element influx in these samples was fluid-mediated. In the garnet-facies samples, amphibole and, interestingly, olivine have similarly high Li concentrations as clinopyroxene, leading to cpx/amphDLi=0.7 and cpx/olDLi=0.7-0.8, the latter being up to ten times lower than in the spinel-facies rocks. Due to its high modal abundance, olivine is the main host of Li in the garnet-amphibole peridotites. The observed metasomatic features provide evidence for the infiltration of an aqueous fluid in the mantle wedge above a subducting slab. This fluid most likely derived from subducted crustal rocks that underwent partial melting. Successive retrograde re-equilibration during exhumation of the garnet peridotite is accompanied by garnet and clinopyroxene breakdown and amphibole formation. This process produced minor changes, such as an increase of HREE and Li in amphibole, and an increase of Li in olivine. The general trace element signature remains essentially unchanged during retrogression and further hydration, indicating that fluids with a similar composition to the one present at the garnet-amphibole peridotite formation, were responsible for increased amphibole formation. The combined evidence from the metamorphic and metasomatic evolution indicates that the peridotites experienced first corner flow in a mantle wedge, followed by subduction and finally entrapment and exhumation within a crustal slab. During their entire history the Ulten peridotites were percolated first by melts and then by aqueous fluids, which added recycled crustal components to the mantle wedge. © Springer-Verlag 2006.